Optimalisasi Media Pembelajaran Wordwall untuk Meningkatkan Minat Belajar Siswa: Perspektif Inovasi Manajemen Pembelajaran di SDN 2 Linggamukti - Yahya, Mohammad; Fauziah, Haifa Luthfy; Warda, Faikatul (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
The learning interest of fourth-grade students at SDN 2 Linggamukti in Islamic Religious Education (PAI & BP), particularly on the topic of the Prophet Muhammad’s migration, was found to be low. This was evident from poor attendance, limited classroom engagement, and unsatisfactory assignment outcomes. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model over two cycles. Data were collected through observation, questionnaires, and interviews, and analyzed using descriptive quantitative methods. Teacher activity increased from 60% to 90%, and student activity from 63% to 93%. The classical mastery level of student learning interest improved from 40% (pre-action) to 67% (cycle I) and 93% (cycle II). The implementation of Wordwall-based interactive learning media effectively improved student learning interest and demonstrated an innovative approach to digital learning management in Islamic elementary education.